Reformulasi Restitusi dalam Tindak Pidana Kekerasan Seksual Terhadap Korban Perempuan dengan Retardasi Mental - Zainur Ratna Savitri; Fanny Tanuwijaya; Yusuf Adiwibowo (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Article 7A paragraph (3) of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, states that